10.1139/facets-2019-0010 - Jessica Bradford; Ramón Filgueira; Megan Bailey (Canadian Science Publishing, 2020)
Aquaculture is one of the world's fastest growing food production sectors and presents an opportunity for rural community development that can support coastal livelihoods. An ecosystem approach to aquaculture (EAA) has been recommended to facilitate socially and environmentally sustainable development, yet there remains a need to better involve people in planning and operational aspects. Community-based management may help to implement principles of the EAA; however, context-specific research is needed to understand its potential application and suitability. This research explores opportunities for community-based marine aquaculture (CBMA) for nonfinfish in the context of Nova Scotia, Canada, through a series of stakeholder interviews. Results suggest that all stakeholder groups interviewed were positive about the potential for CBMA to support sustainable aquaculture growth in the province; however, key questions around operationalizing CBMA remain. The aquaculture industry is on a continual path for growth worldwide and, therefore, it becomes increasingly important to proactively examine strategies such as CBMA that can help to facilitate EAA in a way that genuinely puts people at the centre of aquaculture development and governance.